La búsqueda de una identidad artística. La abstracción en las ideas de Luis Miró Quesada - Schreier Barreto, Christopher (2016)
In Architecture, abstraction was used by modernity to take distance from architectural styles, while looking for volumetric simplicity and denial of past. Luis Miró Quesada developed the concepts of forms and formulas to distinguish architectural composition, as a means of synthesizing the basic forms, different from the other one based on rules of composition related to local styles. In this context of duality, Luis Miró Quesada defines the difference between ornament and decoration; his intention is to emphasize the technical and constructional aspects of buildings, as a composition feature in Modern Architecture.